Uncertainty, scarcity and transparency: Public health ethics and risk communication in a pandemic - Abigail E. Lowe; Teck Chuan Voo; Lisa M. Lee; Kelly K. Dineen Gillespie; Christy Feig; Alva O. Ferdinand; Seema Mohapatra; David M. Brett-Major; Matthew K. Wynia (Elsevier, 2022)
Summary: Communicating public health guidance is key to mitigating risk during disasters and outbreaks, and ethical guidance on communication emphasizes being fully transparent. Yet, communication during the pandemic has sometimes been fraught, due in part to practical and conceptual challenges around being transparent. A particular challenge has arisen when there was both evolving scientific knowledge on COVID-19 and reticence to acknowledge that resource scarcity concerns were influencing public health recommendations. This essay uses the example of communicating public health guidance on masking in the United States to illustrate ethical challenges of developing and conveying public health guidance under twin conditions of uncertainty and resource scarcity. Such situations require balancing two key principles in public health ethics: the precautionary principle and harm reduction. Transparency remains a bedrock value to guide risk communication, but optimizing transparency requires consideration of additional ethical values in developing and implementing risk communication strategies.